Crystallographic Study of Alkali Metal Dichromates - Panagiotopoulos, Nicolas Chrestou (My University, 1972)
The alkali metal dichromates show extensive polymorphism. The crystal structures of the polymorphs α-Na2Cr2O7, β-Na2Cr2O7, β1-Rb2Cr2O7 and P21/c NaRbCr2O7 have been determined with x-ray methods. Crystal data were determined for β2-Rb2Cr2O7, P1 Cs2Cr2O7 and the P21/c NaCsCr2O7.
The dichromate ions found in this work have been compared with the dichromate ions found in other crystal structure determinations. The anions are described in terms of the bridging oxygen angles b and the torsion angles α1 and α2. Many of the dichromate ions are close to having C2v symmetry with values for α1 and α2 close to zero and bridging angles of around 124°. But there is a number of dichromates with α1 = -α2 and 0°<|α|<60° for which the bridging angle varies between 131° to 141°.
The structures determined in this work are discussed as part of a unified description of thortveitite like and dichromate like structures in terms of layers of Y2O7 anions. In terms of this description and Brown and Calvo's classification a structure is proposed for the β2Rb2Cr2O7, while for the structure of NaCsCr2O7 it is suggested that it is isostructural to that of P21/c NaRbCr2O7. The phase transition of α-Na2Cr2O7 to β-Na2Cr2O7 is considered and it is suggested that a twisting thermal mode plays an important role in this as well as in other transitions.
Keywords: crystallographic, study, Alkali metal, dichromates, polymorphs, structures, anions